2015
DOI: 10.1007/s10940-015-9265-6
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Demographic Understanding of Incarceration Disparities: Race, Ethnicity, and Age Structure

Abstract: Objectives Non-Hispanic blacks and Hispanics in the United States are more likely to be incarcerated than non-Hispanic whites. The risk of incarceration also varies with age, and there are striking differences in age distributions across racial/ethnic groups. Guided by these trends, the present study examines the extent to which differences in age structure account for incarceration disparities across racial and ethnic groups.MethodsWe apply two techniques commonly employed in the field of demography, age-stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 26 publications
1
34
0
Order By: Relevance
“…1 These data sets are uniquely well suited to address these research questions, representing the only publicly available and nationally representative data that collects longitudinal information on mothers' health and children's criminal justice contact. Many NLSY79 respondents have children who reached adolescence and early adulthood during the height of the prison boom and are observed near or around their early 30s when incarceration rates are highest (Vogel and Porter 2016).…”
Section: Methodsmentioning
confidence: 99%
“…1 These data sets are uniquely well suited to address these research questions, representing the only publicly available and nationally representative data that collects longitudinal information on mothers' health and children's criminal justice contact. Many NLSY79 respondents have children who reached adolescence and early adulthood during the height of the prison boom and are observed near or around their early 30s when incarceration rates are highest (Vogel and Porter 2016).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to changes in poverty, wealth, segregation, and inequality, other correlates of violence have changed over time in dissimilar ways across racial and ethnic groups. Age, for example, is strongly associated with violent victimization, and youth comprise a greater proportion of Blacks and Latinos than Whites (Vogel and Porter, 2016). 4 Furthermore, the age distributions of each group have changed over time at different rates, with Whites becoming increasingly older, on average, compared to Blacks and Latinos.…”
Section: Prior Researchmentioning
confidence: 99%
“…4.In their assessment of national incarceration rates, Vogel and Porter (2016) found that 20% of the Latino versus White, and 8% of the Black versus White disparities in incarceration rates in 2010 are accounted for by the different age compositions of the groups.…”
Section: Notesmentioning
confidence: 99%
“…Unemployment rates for AA men (14%) are higher than White men (6.7%; US Bureau of Labor Statistics, ). One in 13 AA men in their 30's is incarcerated, a rate that is greater than non‐AA men (Vogel & Porter, ). Rates of poverty in AA men (26%) are higher than nonminority White fathers (14%; Macartney, Bishaw, & Fontenot, ; Minton & Zeng, ).…”
Section: Introductionmentioning
confidence: 99%